Edward Irving on the Sinful Human Nature of Christ: A Response and Critique from an Arminian/Adventist Perspective - Whidden, Woodrow W. (Journal of Asia Adventist Seminary, 2009)
Edward Irving argued that Christ during the incarnation assumed humanity's fallen, sinful human nature. He made it clear though, that Christ never committed actual acts of sin. He affirmed that Christ was fully God and fully human, yet qualified his stance that Christ's divinity was quiescent during the incarnation. He attributed Christ's victory in sinful flesh to the power of the Holy Spirit and therefore sinless living is possible as well for fallen humanity, with the aid of the same power. Irving's attempt to establish that sinless living is possible through Christ's condescension to the same level of fallen humanity, while noble, essentially results in a Christology that is questionable. This study attempts to prove that it is not necessary for Christ to assume sinful human nature in order for Him to be humanity's Savior. Moreover this study proves that although Christ's human nature was sinless, yet He holds no distinct advantage over our humanity in our struggles against temptations.